PELAKSANAAN KEWAJIBAN DIVESTASI SAHAM DALAM RANGKA PENANAMAN MODAL ASING DI BIDANG PERTAMBANGAN MINERAL DAN BATUBARA PASCA TERBITNYA UNDANG-UNDANG NOMOR 3 TAHUN 2020 TENTANG PERUBAHAN ATAS UU NOMOR 4 TAHUN 2009 TENTANG PERTAMBANGAN MINERAL DAN BATUBARA - Bagus Prasetyawan (UNES Law Review, 2023)
In article 7 of Law Number 25 of 2007 (UU 25 of 2007) stipulates that the government's authority is not to carry out nationalization actions or to take investment ownership rights, except by law. However, specifically for investment and implementation of mineral and coal mining business activities, the obligation to nationalize or divest shares has been regulated in Article 112 of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining (UU 3 of 2009). 2020) which states that business entities holding mining business licenses at the stage of production operations whose shares are owned by foreigners are required to divest shares of 51% (fifty-one) percent in stages to the central government, regional governments, BUMN, regionally owned enterprises, and national private business entity. Holders of mineral and coal mining business licenses for foreign investment who do not carry out their divestment obligations by referring to the mechanism of laws and regulations in the field of mineral and coal mining may be subject to administrative sanctions under the provisions of Article 151 of Law 3 of 2020 and Article 147 of Government Regulation Number 96 of 2021 concerning Implementation of Mineral and Coal Mining Business Activities (PP 96 of 2021), in the form of written warnings, temporary suspension of part or all of business activities, and revocation of mining business permits if they do not carry out the obligation to divest shares.